Interpreting the Influence of Heuristic and Systematic Cues on Visual Attention to Food Label Claims - Caitlin Stanton; Courtney Meyers; Nan Li; Amber McCord (Journal of Applied Communications, 2024)
An increase in consumer concern surrounding food ingredients has triggered a rise in label claims as an attempt to communicate salient product attributes to influence a purchase decision. Previous research has established the use of food label claims as heuristic cues, facilitating quick decisions without the need for complicated cognitive processing. Design of a label claim becomes an important concern as research has indicated distinct design elements promote further processing. This study sought to understand the role of visual and textual elements of a label claim toward dual processing routes through the use of eye tracking measures. The results indicated label claims that included both visual and textual elements elicited the highest visual attention allocation from consumers, and suggested that label claims are processed systematically in addition to heuristically as previously specified. Future label claims should include both visual and textual elements to promote further cognitive processing among all consumers. The findings from this study provide an avenue for greater understanding of dual processing modes within the context of food label claims and other agriculturally-relevant concepts.
Keywords: Heuristic-Systematic Processing Model; eye tracking; visual attention; food label claims; food marketing